ANALISIS NILAI KARAKTER MANDIRI DI PESANTREN DAR EL-HIKMAH KECAMATAN TAMPAN KOTA PEKANBARU - Nila Normandia; Zahirman '; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: This research is motivated phenomenon are still many students who are not able to carry out their work independently, such as making the bed individually, to prepare for school, set up a schedule of study and prayer. Independent attitude is very necessary is grown on each students themselves. The problem of this study is How Values Of Independent Character In Pesantren Dar El-Hikmah Tampan Subdistrict Pekanbaru City. No matter the purpose of this study was to determine the Values Of Independent Character In Pesantren Dar El-Hikmah Tampan Subdistrict Pekanbaru City. This research was conducted in Pesantren Dar El-Hikmah Tampan Subdistrict Pekanbaru City. The population in this study was 26 caretakers and 1,513 children in foster care. While the sampling technique in this research is total sampling techniques and sample proportional. Data collection techniques by observation, using a questionnaire, Interview, and documentation. In analyzing the data this study uses quantitative data analysis techniques. These results indicate that the Values Of Independent Character In Pesantren Dar El-Hikmah Tampan Subdistrict Pekanbaru City in the category GOOD with 42.32% and the percentage of category LESS WELL with the percentage of 57.68%. Then the hypothesis are accepted. Key Words: Values, Character, Independent .